Trial of Deferiprone in Parkinson's Disease - Devos, David; Labreuche, Julien; Rascol, Olivier; Corvol, Jean-Christophe; Duhamel, Alain; Guyon Delannoy, Pauline; Poewe, Werner; Compta, Yaroslau; Pavese, Nicola; Růžička, Evžen; Dušek, Petr; Post, Bart; et al. (The New England journal of medicine, 2022)
BACKGROUND: Iron content is increased in the substantia nigra of persons with Parkinson's disease and may contribute to the pathophysiology of the disorder. Early research suggests that the iron chelator deferiprone can reduce nigrostriatal iron content in persons with Parkinson's disease, but its effects on disease progression are unclear. METHODS: We conducted a multicenter, phase 2, randomized, double-blind trial involving participants with newly diagnosed Parkinson's disease who had never received levodopa. Participants were assigned (in a 1:1 ratio) to receive oral deferiprone at a dose of 15 mg per kilogram of body weight twice daily or matched placebo for 36 weeks. Dopaminergic therapy was withheld unless deemed necessary for symptom control. The primary outcome was the change in the total score on the Movement Disorder Society-sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS; range, 0 to 260, with higher scores indicating more severe impairment) at 36 weeks. Secondary and exploratory clinical outcomes at up to 40 weeks included measures of motor and nonmotor disability. Brain iron content measured with the use of magnetic resonance imaging was also an exploratory outcome. RESULTS: A total of 372 participants were enrolled; 186 were assigned to receive deferiprone and 186 to receive placebo. Progression of symptoms led to the initiation of dopaminergic therapy in 22.0% of the participants in the deferiprone group and 2.7% of those in the placebo group. The mean MDS-UPDRS total score at baseline was 34.3 in the deferiprone group and 33.2 in the placebo group and increased (worsened) by 15.6 points and 6.3 points, respectively (difference, 9.3 points; 95% confidence interval, 6.3 to 12.2; P<0.001). Nigrostriatal iron content decreased more in the deferiprone group than in the placebo group. The main serious adverse events with deferiprone were agranulocytosis in 2 participants and neutropenia in 3 participants. CONCLUSIONS: In participants with early Parkinson's disease who had never received levodopa and in whom treatment with dopaminergic medications was not planned, deferiprone was associated with worse scores in measures of parkinsonism than those with placebo over a period of 36 weeks. (Funded by the European Union Horizon 2020 program; FAIRPARK-II ClinicalTrials.gov number, NCT02655315.).
Keywords: Deferiprone; antiparkinsonika; Levodopa; Substantia Nigra; Administration, Oral; levodopa; progrese nemoci; Dopamine Agents; Brain; železo; aplikace orální; dopaminové látky; Iron Chelating Agents; chelátory železa; neutropenie; Disease Progression; dvojitá slepá metoda; Neutropenia; deferipron; lidé; Iron; Humans; mozek - chemie; mozek; Brain Chemistry; Antiparkinson Agents; substantia nigra; Double-Blind Method; Parkinson Disease; Parkinsonova nemoc